A pathway to PDS partnership : using the PDSEA protocol - Shoemaker, Emily; Cosenza, Michael N.; Kolpin, Thierry; Allen, Jacquelyn May (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Professional Development Schools offer P-12 schools and universities the opportunity to create rich learning environments for students, teacher candidates, teachers, university professors and administrators. The creation of Professional Development Schools requires careful thought and planning by leaders from both institutions who understand the importance of a systemic approach to gathering information that will allow them to build strong, sustainable partnerships. This book is a practical, hands-on guide to exploring and assessing school and university readiness and compatibility to pursue a PDS partnership. The Professional Development School Exploration and Assessment (PDSEA) Protocol provides surveys and focus group interview questions that facilitate the identification of P-12 school and teacher preparation program qualities, characteristics and perceptions to determine institutional compatibility. Collaborative discussion and PDS planning templates provide guidelines for planning new PDSs. The authors offer unique insights into Professional Development Schools based on their experiences as educators in elementary, middle school, high school and as university professors who have been active in Professional Development Schools for 13 years. In this book, they share their insights and practical ideas about what it takes to develop viable and sustainable Professional Development Schools. Developed over a period of 8 years in a study that involved three universities and 13 partner schools, the PDSEA Protocol will assist teacher preparation programs, P-12 school districts and individual school sites as they explore, assess and plan school-university partnerships"-- Provided by publisher.
Keywords: Laboratory schools -- United States.; College-school cooperation -- United States.; Teachers -- Training of -- United States.; Education -- Evaluation & Assessment.; Education: examinations and assessment.; elektronické knihy; electronic books